Penerapan Metode Talaqqi pada Siswa dalam Menghafal Al-Qur’an di Siswa Smks Budi Agung Marelan - Muhammad Eka Prasetia (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
Memorizing the Qur’an is a process to maintain, protect, and preserve its purity. It is considered a noble task and responsibility that requires consistency, patience, and proper guidance. While everyone has the potential to memorize the Qur’an, not all individuals are able to do it effectively. Various factors influence the success of memorization, including the use of suitable methods. One of the effective approaches is the Talaqqi method, which emphasizes direct learning and repetition under the guidance of a teacher. This study aims to examine the application of the Talaqqi method among students at SMKS Budi Agung Marelan in their efforts to memorize the Qur’an. The research employed a qualitative field research design using interviews, observation, and documentation as data collection techniques. The findings reveal that the implementation of the Talaqqi method consists of three main stages: preparation, implementation, and evaluation. Furthermore, several supporting factors were identified, such as teacher guidance, students’ intrinsic motivation, and a supportive learning environment, all of which significantly contribute to successful Qur’an memorization.